Shear failure of the Meraka hardwood in bolted connections loaded parallel to the timber grain - Abdul Razak, Abdul Karim; Quenneville, Pierre; Norazzlina, M.Sa‘don (IOP Publishing, 2021)
This current study was conducted to establish a bolted connection experimental database on Malaysia woods. The effort of improving the retrofit guideline in designing the wall-diaphragm connections of masonry buildings can be continuously done. Brittle failure verifications on the Meraka hardwood to verify the occurrence of row shear failure are presented in this paper. The hardwood species was selected due to its common use as structural rafters and joists in the construction of roof and floor diaphragms of masonry buildings, respectively. Ten groups of a single row of steel-wood-steel (SWS) connections loaded parallel to the timber grain were tested. Each group was prepared with a total of ten replicates of specimens. Comparisons of bolted connection strength between the experimental results and the predictions of the existing design equations are discussed. It was found that the timber standard of Malaysia (MS544) too conservative in estimating the strength, whilst the Row Shear Model (RSM) is more comparative.